Determinants of Innovation: Malaysian Perspectives - Tam, Peter Hong Shiung (2009)
This paper aims to identify the determinants of innovation based on the perceptions of executives from the industry in Malaysia. The study will further investigate the differences in perceptions about determinants of innovation in Malaysia by several demographic groups such as age, managerial responsibilities, job role, firm ownership, industry and MSC Status of firms. An online survey was designed to test five determinants of innovation identified from literature for their relevance to the Malaysian context. The data are further tested using factor analysis and linear regression tests to further identify the underlying dimensions or factors and their impact on innovation; and independent sample t-tests to identify the differences in perceptions by demographic groups. All five determinants of innovations from literature are found to be relevant to Malaysian firms and that only the dimension of external factors have a significant impact on innovation. It was also found that there are no significant differences in perceptions between age groups, managerial responsibilities, technical roles and MSC Status; whereas differences exists between foreign owned firms and local organisations; and ICT firms and non-ICT firms. It is hoped that the findings will provide guidance to managers and policy makers to focus on specific initiatives and efforts to improve the conditions that will drive innovation for Malaysian firms.